Evaluation of Serum Interleukin-33 and Tumor Necrosis Factor-α Levels in Patients with Psoriasis: Correlation with Disease Severity - Mohammed Gharib, Tanya Kamil; Hassan, Ali Hussein (Kurdistan Journal of Applied Research, 2025)
Psoriasis is an immune-mediated dermatological disorder marked by accelerated skin cell proliferation, leading to thickened, rough, scaly lesions capable of causing itching, discomfort, and inflammation. This study investigates Interleukin-33 (IL-33) in psoriasis pathogenesis and evaluates its therapeutic potential. By understanding its mechanisms, the research aims to create effective treatment strategies for use in clinical practice, improving the well-being of individuals with the disease. Serum concentrations of Interleukin-33 and tumor necrosis factor-α (TNF-α) were assessed using the ELISA test in 44 subjects with psoriasis and 44 matched healthy controls. The severity of psoriasis was evaluated using Psoriasis Area and Severity Index (PASI scores), which enabled stratification into mild, moderate, and severe forms. Data were statistically analyzed to compare cytokine levels in patients and controls and to examine the relationship between cytokine concentrations and disease severity. Compared to their matched controls, psoriasis patients exhibited significantly increased median concentrations of Interleukin-33 [(268: 235–316) and tumor necrosis factor-α (294: 241–435). Also, the serum TNF-α levels exhibited a notable correlation with PASI scores (r= 0.389, p value= 0.009), while IL-33 levels did not exhibit a statistically significant association with PASI scores (r= 0.251, p value= 0.100). This study demonstrated a significant elevation in serum TNF-α and IL-33 concentrations in individuals with the disease, suggesting their involvement in disease pathogenesis. Moreover, TNF-α levels showed a proportional correlation with disease severity, as reflected by PASI scores, indicating its potential role as a biomarker for monitoring psoriasis progression. This positive association suggests a possible interplay in disease progression.